Russian beach volleyball at the olympic games: results, problems, prospects - Kostyukov V.V. ,; Nirka V.V. ,; Fedotov D.E. ,; Karlitsky I.N. ,; Kostyukova O.N. , (Theory and Practice of Physical Culture, 2023)
Objective of the study was to assess the quality of performance of competitive actions by players of the best 16 men's and women's teams participating in the Olympic beach volleyball tournaments in the program of the XXXII Olympic Games of 2021 in Tokyo (Japan). Results and conclusions. The ranked values of the performance of players in performing offensive strikes, blocking and serves, given in the illustrations, make it possible to identify their average group values, which are conditional guidelines for Russian athletes and athletes preparing to participate in the XXXIII Olympic Games of 2024 in Paris (France) and others major international beach volleyball competitions. Recommendations and wishes developed based on the results of the study to athletes and coaches aim them at specific actions that will help improve the quality of pre-Olympic preparation processes in beach volleyball.